Nursing care strategies on violence against women - Acevedo López, María Nallely (2023)
Violence against women by their partners continues to be a social problem linked to stereotypes and behaviors derived from patriarchal systems that normalize violent acts against this population group. However, it also continues to be a public health problem, since violence has consequences that go beyond the physical for women who are victims of violent acts. The objective of this paper is to describe nursing care strategies on violence against women. The concept of deconstruction constitutes a proposal that intends to structure a form of intellectual revolution where dominant proposals would be dismantled. In this sense, it is proposed that nursing should enter into a process of deconstruction and at the same time promote the deconstruction of the ideas surrounding the gender perspective itself in order not to stigmatize women victims of violence. Likewise, the authors propose a solid promotion of women's health through the strengthening of the discipline in strategies that allow not only to prevent, but also to promote the change of paradigms around gender and the role of women in society.